1996
DOI: 10.1016/s0022-5223(96)70160-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide activity in patients undergoing cardiopulmonary bypass

Abstract: It is well known that cardiopulmonary bypass (CPB) causes major hemodynamic and physiologic disturbances. These may be alleviated by replacing conventional nonpulsatile perfusion with pulsatile flow, which under normothermic conditions results in a lower peripheral vascular resistance, associated with lower plasma angiotensin II and vasopressin levels, t, 2 It is also known that release of the endogenous vasodilator nitric oxide (NO) is sensitive to flow pulsatility, 3' 4 a mechanism that may contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…The beneficial effects of pulsatile flow on microcirculatory perfusion are in agreement with findings by others who showed that pulsatility reduced markers of endothelial damage and improved gastric mucosal oxygenation and tonometry (24,28). Here we confirm these findings by direct measurements of microcirculatory perfusion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The beneficial effects of pulsatile flow on microcirculatory perfusion are in agreement with findings by others who showed that pulsatility reduced markers of endothelial damage and improved gastric mucosal oxygenation and tonometry (24,28). Here we confirm these findings by direct measurements of microcirculatory perfusion.…”
Section: Discussionsupporting
confidence: 93%
“…A recent crossover study by Elbers et al (10) showed no difference in microcirculatory perfusion after 10 min of either pulsatile or nonpulsatile CPB, but their conclusions were limited by the study design. In contrast, laser-Doppler flow or gastric tonometry measurements indirectly indicated that pulsatility may preserve microvascular perfusion (13,24,28). At similar mean arterial pressures, pulsatile flow was associated with a 10 -15% more energy equivalent pressure than nonpulsatile flow (37), which has previously been suggested to be a prerequisite to overcome the critical capillary closing pressure (43).…”
mentioning
confidence: 89%
“…In the majority, different perfusion modes are given to the same subject following one another, but this change in perfusion modality affects other mechanisms involved in NO release (11)(12)(13), and consequently alters NO release measurement. Moreover, only few studies concern the analysis of human patients undergoing cardiac surgery (14)(15)(16).…”
mentioning
confidence: 99%
“…Balligand et al recently published a complete review about this phenomenon. 4 Many studies concerning ex vivo analyses of released NO 4,5 or in vivo studies on animals or humans who underwent CPB under different perfusion modalities 4,[6][7][8][9][10] can be found in the literature. However, despite the large number of ex vivo or animal studies, only a few papers deal with human patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%